Agricultural zoning of Coffea arabica in Brazil for current and future climate scenarios: implications for the coffee industry - Lorençone, João Antonio; de Oliveira Aparecido, Lucas Eduardo; Lorençone, Pedro Antonio; Torsoni, Guilherme Botega; de Lima, Rafael Fausto; da Silva Cabral de Moraes, José Reinaldo [UNESP]; de Souza Rolim, Glauco [UNESP] (Springer Nature, 2025)
Coffee is an important crop in the global market, being produced in several countries, such as Brazil, Vietnam, Colombia, Ethiopia, and India. Brazil is the world’s largest producer (1.5 million ha), playing an important role in generating jobs and income, especially for family farmers. Coffee is very susceptible to climate and may have high or low yields depending on air temperature and rainfall during the production cycle. Thus, this study aimed to carry out climate zoning for the cultivation of Arabian coffee under different climate change scenarios recommended by IPCC to measure the future impact of climate on Brazilian coffee. The study was carried out for the entire Brazilian territory, using data on annual mean air temperature, mean air temperature of November, mean air temperature of the coldest month, and cumulative annual mean water deficit obtained from the Meteorological Database for Teaching and Research (BDMEP) of the National Institute of Meteorology of Brazil—INMET, covering the period 1960–2020. Moreover, the BCC–CSM 1.1 climate model, with a resolution of 125 × 125 km, collected from the WorldClim 2 platform for 2041 to 2080, using the Representative Concentration Pathway (RCP) 2.6, 4.5, 6.0, and 8.5 scenarios, was employed to obtain future climate data. Brazil has well-defined regional seasons, normally with a hot, humid summer and a cold, dry winter. The country showed great climate variability among regions, with the Northeast region showing the highest values for air temperature and water deficit, the North region concentrating the lowest values of water deficit, and the South region showing the lowest air temperatures. All future climate change scenarios showed a reduction in the total areas suitable for coffee cultivation in Brazil, with a mean reduction of 50%. Furthermore, areas with restrictions due to thermal excess and water deficiency were the most common throughout the country in future scenarios, with a mean of 63% of the entire territory. The most affected regions were Minas Gerais, São Paulo, and Paraná. Future climate changes may negatively affect coffee cultivation in all the studied RCP scenarios.
Keywords: Agrometeorology; Climate modeling; IPCC; Severe droughts